Literature Review: Hubungan Asupan Protein, Vitamin C, dan Zat Besi dengan Kejadian Anemia pada Remaja Putri - Ika Savitri Salsabil; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Anemia is a global health problem and has a high prevalence in various countries. Based on the results of Riskesdas 2018, it's known that there was an increase in anemia in Indonesia which was 48,9%. Adolescent girls have a higher risk of anemia than adolescent boys because adolescent girls have menstrual cycles every month. In addition, adolescent girls also have unhealthy eating patterns, such as extreme diets, with the aim of achieving the ideal figure. Based on several studies, intake of protein, vitamin C and iron has a correlation with anemia among adolescent girls. Objectives: The aim of this literature review is to determine the correlation between intake of protein, vitamin C and iron with anemia among adolescent girls Methods: The research method used is literature review method by choosing a cross sectional design. Discussion: The results of a review of twelve articles showed that 8 of 12 literature reviews showed a correlation between intake of protein with anemia among adolescent girls, 8 of 12 literature reviews showed no correlation between intake of vitamin C with anemia among adolescent girls and 6 of 12 literature reviews showed a correlation between intake of iron with anemia among adolescent girls. Conclusions: Intake of nutrients such as protein, vitamin C and iron will affect the incidence of anemia among adolescent girls.